Structural and parametric optimization of power structures, remotely-piloted aircraft for operational natural resources and ecological environment monitoring - Зосімович, М.В. (Proceedings of National Aviation University (archive), 2007)
For specific design object was posed and solved a decomposition task of a structure of force constructions by distant controlling of fighting vehicles for operating natural and environmental ecological monitoring on early design stages.